(untitled) (Mustansiria Dental Journal, 2022)
ABSTRACT Aim: This study was aimed to evaluate the quality of CPoint obturation system by calculating the percentage of surface area of voids and gaps in different levels in comparison with Guttapercha point/GuttaFlow 2 and Guttacore/Endofill. Method: Sixty palatal roots of extracted upper first molars were prepared and divided into three groups of 20 samples each, the first group was obturated with CPoint/BC sealer, the second one was obturated with Guttapercha point/ GuttaFlow2 and the third was obturated with GuttaCore/Endofil. Each root sectioned into four sections at 8 mm, 6 mm, 4 mm, and 2 mm levels from the W.L and transferred to be photographed under digital microscope, the canal cross sectional area, and the area of voids and gaps were measured then surface area percentages of unfilled areas were calculated. Data then analyzed statistically using ANOVA and LSD tests. Results: Higher percentages of unfilled areas were observed in Group1 (p < 0.01) in comparison to Group2 and Group3 except with S2 of Group3 (p > 0.05). And there was no significant difference between Group2 and Group3 except at S2. The results of comparison among different sections within each group showed that there is a highly significant difference (p < 0.01) between S2and (S8, S6, S4) within Group 1, in Group 2 the results showed that there is a highly significant difference between S8 and the other sections, and also showed a significant difference (p < 0.05) between S2 and (S4, S6). Within Group 3 the results revealed significant difference between the (S4, S6) and the (S8, S2) sections. Conclusion: All systems showed voids and gaps and CPoint obturation system showed the highest percentage of unfilled areas and level of root section had an effect on voids and gaps distribution.